The Effect of Overtime Work and Work Environment on Employee Performance Through Job Satisfaction at PT Bio Farma (Persero) - Mochamad Ridwan; R. Ervin Agung Priambodo (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine the effect of overtime on employee performance, the effect of work environment on employee performance, the effect of overtime on employee performance mediated by job satisfaction, the effect of work environment on employee performance mediated by job satisfaction, and the effect of job satisfaction on employee performance. This research was conducted at PT Bio Farma (Persero) with a sample size of 237 people. The method used was quantitative with data collection techniques using questionnaires. Statistical testing used SEM PLS (Structural Equation Modeling Partial Least Square) to measure the relationship between variables. The results showed that the work environment and job satisfaction have a direct positive and significant effect on performance. Furthermore, overtime work and the work environment have a positive and significant indirect effect on performance through job satisfaction, while overtime work has a direct negative and nonsignificant effect on employee performance. This research can have good implications for companies and leaders in efforts to improve employee performance by implementing appropriate overtime work policies, maintaining a conducive work environment, and not neglecting job satisfaction as a positive booster for employees.